2004
DOI: 10.1248/bpb.27.232
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of .BETA.-Cryptoxanthin Induces Anabolic Effects on Bone Components in the Femoral Tissues of Rats in Vivo

Abstract: Bone loss with aging induces osteoporosis, which is widely recognized as a major public health problem.1-3) A decrease in bone mass leads to bone fracture. Bone loss may be due to decreased bone formation and increased bone resorption. Pharmacologic and nutritional factors are needed to prevent bone loss with increasing age. Chemical factors in food may help to prevent bone loss with aging.4) The chemical compounds in food which act on bone metabolism, however, are poorly understood.Recent studies have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
(29 reference statements)
0
35
1
Order By: Relevance
“…39) β-Cryptoxanthin (10, 25 or 50 µg/100 g body weight) was orally administered once daily for 7 days to young male rats. 39) The administration of β-cryptoxanthin (25 or 50 µg/100 g body weight) caused a significant increase in calcium content, alkaline phosphatase activity, and DNA contents in the femoral-diaphyseal and -metaphyseal tissues. Such an effect is also observed in the femoral tissues of aged (50-week-old) female rats.…”
Section: Effect Of β-Cryptoxanthin In Animal Models For Osteoporosismentioning
confidence: 99%
“…39) β-Cryptoxanthin (10, 25 or 50 µg/100 g body weight) was orally administered once daily for 7 days to young male rats. 39) The administration of β-cryptoxanthin (25 or 50 µg/100 g body weight) caused a significant increase in calcium content, alkaline phosphatase activity, and DNA contents in the femoral-diaphyseal and -metaphyseal tissues. Such an effect is also observed in the femoral tissues of aged (50-week-old) female rats.…”
Section: Effect Of β-Cryptoxanthin In Animal Models For Osteoporosismentioning
confidence: 99%
“…4B). Discussion ß-cryptoxanthin has been shown to have a stimulatory effect on osteoblastic bone formation in vitro (6,7) and in vivo (10)(11)(12) by stimulating osteoblastic cell proliferation and differentiation and by regulating osteoblastic gene expression, including Runx2 a master regulator of osteoblast differentiation (26,28), the matrix protein of ·1 (I) collagen (6,29), and alkaline phosphatase which participates in the mineralization process (6,30). The molecular mechanism by which ß-cryptoxanthin promotes osteoblast differentiation is, however, poorly defined.…”
Section: ß-Cryptoxanthin Stimulates Osteoblastic Mineralizationmentioning
confidence: 99%
“…), has anabolic effects on osteoblastic bone formation (4-7) and suppressive effects on osteoclastic bone resorption in vitro (5,8,9), leading to an increase in bone mass. Furthermore, oral administration of ß-cryptoxanthin was shown to have anabolic effects on bone turnover in young and aged rats (10), and prevents bone loss in streptozotocin-diabetic rats (11), and ovariectomized rats (12) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The oral administration of ß-cryptoxanthin has been shown to induce an anabolic effect on bone components in the femoral-diaphyseal (cortical bone) and -metaphyseal (trabecular bone) tissues in young and aged rats in vivo (13,14). Moreover, it has been found that streptozotocin-induced bone loss in rats with a diabetic state is prevented by the oral administration of ß-cryptoxanthin in vivo (15).…”
Section: Introductionmentioning
confidence: 99%